The Understanding of Pediatric Akinetic Mutism - Severo Bem, Luiz (Cureus, 2021)
Pediatric akinetic mutism syndrome is a clinical disease resulting from cerebellar injury and characterized by the absence of speech or reduced speech, emotional lability, there may also be hypotonia, oropharyngeal dysfunction/dysphagia, bladder and intestinal incontinence, or other behavioral disorders and neurological signals. It is described as the most recurrent complication in children, after posterior fossa tumor surgery, mainly related to cerebellar midline injuries. An increasing number of research and prospective reviews have provided valuable information on cerebellar mutism syndrome in recent years. The purpose of this review was to elucidate the pathophysiological basis and the predictive factors for this syndrome. Most cases of mutism are due to injury cerebellar tracts and cerebellar-cerebral circuits, involving particularly distinct points of the dentate-thalamus-cortical and dentato-rubro-thalamus-cortical. Advanced neuroimaging techniques, such as tractography and perfusion studies, have contributed to demonstrating changes in these pathways in patients with pediatric cerebellar mutism.